Register allocation for programs in SSA Form - Hack, Sebastian (KIT Scientific Publishing, 2021)
This book investigates register allocation for programs in static single-assignment form.Its main result is that the interference graphs of SSA-form programs are chordal.This gives the compiler precise knowledge over the register demand and allows for separating spilling, assignment and coalescing. For each of these phases, we present methods specially tailored to the SSA setting and provide a first evaluation.